Effectiveness of (PjBL) Assisted by Audiovisual Media Speaking Skills in News Texts for Grade VII - Ersa Alami; Maulina Fitria (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
Learning speaking skills can improve students' ability to express their opinions logically through critical thinking. In addition, speaking skills can also shape students' character to be brave in expressing their opinions with confidence, as well as learning to respect the opinions of others. During the learning process, students are expected to be brave enough to express their opinions and ask questions in discussion forums. However, it is often found that students tend to feel shy and hesitant in expressing their opinions. Therefore, the researcher was interested in studying the application of the project-based learning model in Indonesian language learning of news text material for grade VII at SMPN 7 Bangkalan. This study used a descriptive qualitative research method with 29 seventh-grade students in class VII-B at SMPN 7 Bangkalan as the research subjects. The data collection techniques used in this study were: (1) observation; (2) interviews; and (3) performance tests. The results of this study show that there were 3 students who did not meet the qualifications. However, there were 26 students who met the qualifications. Thus, it can be concluded that the project-based learning model is effective in teaching Indonesian language news text material in class VII-B at SMPN 7 Bangkalan.